Impacto microeconómico de la financiarización en las peque\~nas empresas: El caso espa\~nol - Nazaret Abalde; Fernando González Laxe; Federico Martín Palmero; Matilde Massó (Atlantic Review of Economics (ARoEc), 2022)
– Empirically, financialisation analysis can be addressed from either a macroeconomic or micr oeconomic perspective. In aggregate terms, the former implies observing the growing influence exerted by financial transactions, overly dominant financial markets and alterations to industrial economy logics by global finances. As for the latter, the micro economic approach aims to study financialisation from within companies through the analysis of their financial reports and income statements. Our research aims to interrelate both spheres from an empirical approach in order to determine the existence o f a causal relation between them. It was conducted using a database of 42,873 Spanish manufacturing companies with fewer than 100 employees and the calculation of a financialisation rate for the period 1995 - 2017. The results revealed that from a macroecono mic perspective, financialisation was a key factor in the recent crisis, and that this crisis brought about changes to corporate behaviour trends, consisting of a move away from fixed capital and profit investments, demonstrating the existence of a 'scisso r effect' in both cases.
Keywords: E44; G35; M41; 330; Microeconomía; Financiarización; Pymes. Espa\~na; Microeconomics; Financialization; SMEs. Spain